CODE MIXING IN A NOVEL CELEBRITY WEDDING BY ALIAZALEA - Mangantar Sitohang; Fitri Ermawati (STIBA IEC JAKARTA, 2019)
This study is aimed to describe code mixing facts or presence in the novel Celebrity Wedding by AliaZalea. In fact, there are a lot of factors that influence people using code mixing, to mention one or two, can be due to someone’s bilingualism or multilingualism condition. The writers use descriptive and content analysis method to analyze the forms code mixing, the types of phrases and compound of code mixing found in the novel Celebrity Wedding. The (English) data taken from the Novel are phrases, compounds. The writers then identified, collected, sorted and classified all the data, and made the analysis to find and determine the types of the phrases and the forms/types of modifiers present in the novel itself. From the result of analysis/discussion there are more Noun Phrase Types than Verb Phrase Types. There are five Noun Phrases containing premodifiers and four postmodifiers five containing both premodifiers, the dominant modifiers are Adjective followed by Noun the Preposition Phrases.